2021
DOI: 10.1519/jsc.0000000000003936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training Performed to Failure or Not to Failure on Muscle Strength, Hypertrophy, and Power Output: A Systematic Review With Meta-Analysis

Abstract: Vieira, AF, Umpierre, D, Teodoro, JL, Lisboa, SC, Baroni, BM, Izquierdo, M, and Cadore, EL. Effects of resistance training performed to failure or not to failure on muscle strength, hypertrophy, and power output: A systematic review with meta-analysis. J Strength Cond Res 35(4): 1165–1175, 2021—The aim of this review was to summarize the evidence from longitudinal studies assessing the effects induced by resistance training (RT) performed to failure (RTF) vs. not to failure (RTNF) on muscle strength, hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 49 publications
1
54
1
6
Order By: Relevance
“…The increased body weight might result in enhanced grip power in HPHF. A recent review revealed that resistance training could increase muscle strength [ 40 ]. In our study, the 8-week training enhanced grip power in the Con groups.…”
Section: Discussionmentioning
confidence: 99%
“…The increased body weight might result in enhanced grip power in HPHF. A recent review revealed that resistance training could increase muscle strength [ 40 ]. In our study, the 8-week training enhanced grip power in the Con groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the latest evidence on strength training support that using low loads, low volume and not-to-failure repetitions produce considerable improvements in maximal dynamic strength, power output and muscle hypertrophy while preventing typical discomfort, fatigue or stiffness after traditional high-demanding training [ 95 , 96 , 97 ]. This is important given that people with post-COVID-19 syndrome are expected to be reluctant to engage in exercise due to fatigue, deconditioning and low tolerance to exercise intensity.…”
Section: The Potential Role Of Exercise In Post-covid-19 Syndromementioning
confidence: 99%
“…A subsequent meta-analysis by Vieira et al (175) found that training to failure promoted greater increases in muscle mass compared to non-failure protocols, with a relatively large magnitude of effect (ES = 0.75 [95% CI 0.22 to 1.28]). Discrepancies in the findings between the two meta-analyses can be attributed, at least in part, to differences in study inclusion; the study by Grgic et al (172) included data from 7 studies whereas the study of Vieira et al (175) included only 4 studies.…”
Section: Evidence From the Literaturementioning
confidence: 99%